Staff nurses perceptions of the impact of long stay oncology admission on family relationships. - Brown, Amy (2014)
Having a child diagnosed with cancer is a life changing event affecting all members of the family. Aside from factors such as anxiety, separation and financial strain, family relationships tend to be impacted upon as a result of admission. This study identifies paediatric oncology nurses’ perceptions of this impact on family relationships during long stay oncology admission. In order to ascertain these perceptions, semi-structured interviews were carried out with six nurses working on an oncology ward. Analysis of the interview data found that while some nurses were able to identify positive impacts on family relationships, nurses felt that a childhood cancer diagnosis can have detrimental effects on family relationships. Furthermore, nurses identified that service provision should be improved to ensure that these families feel supporting during this difficult time. Recommendations for nursing practice include implementation of a policy or protocol; improved education for nurses when approaching this sensitive issue and finally, improvement in services to provide advice and support specific to family relationships.